Structure Analysis of Secondary Rubber Side Bearer Pad for Locomotive - 林立钿; 张亚新; 许呈祥; 艾敏 (机车电传动)
Structure of a spherical rubber pad was introduced. With the comparison of FEA analysis and test results to flat round rubber pad, spherical round rubber pad was proved to have better vertical-shear-stiffness matching and fatigue behavior.